Birth Order, parental health investment, and health in childhood - Gerald J. Pruckner; Nicole Schneeweis; Thomas Schober; Martina Zweimüller (Johannes Kepler University of Linz, Department of Economics, 2019)
Research has shown that cognitive and non-cognitive skills, education and earnings decrease with birth order. Less is known about birth order effects on health. This paper provides a comprehensive analysis of the relationship between birth order, health at birth and in childhood, and parental health investment. High-quality administrative data on children born in Austria between 1984 and 2015 allow us to exploit within-family variation in birth order to account for confounding familylevel factors. In a sample of families with two to four children, we find statistically significant and quantitatively important birth order effects on health at birth and in primary school. These birth order effects are positive, in that later-born siblings are healthier than the first-born child, and increase with birth order. Consequently, first-born children are more likely to consume medical drugs and to utilize inpatient and outpatient medical services. We also find significant birth order differences in parental health investment. Compared to their later-born siblings, first-born children are more likely to receive preventive medical care and immunization against measles, mumps, and rubella.
Keywords: I10; I12; I14; J12; J13; 330; Birth order; parental health investment; parental health behavior; health at birth; health in childhood; health care utilization